FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN TOTAL QUALITY MANAGEMENT PAD A PENDIDIKAN TINGGI - Fefri Indra Arza (Journal of Management and Business, 2008)
This research aimed to find empirical evidence about critical success factors that influence of TQM implementation on public sector. The population in this research was public sector on the higher education, with sample from the chairman and secretary of study program on A accreditation economics faculty. Literature studies are done to find factors which determine the success of TQM implementation in public sector. Regression analysis had been used to test the applied hypotheses. Management commitment, education and training, and customer satisfaction orientation factors gave the biggest individual influence on the success of TQM implementation, and statistically had significant positive influence. Concept’s implementation and TQM’s technique gave positive influence on the organizational performance on public sector on higher education in Indonesia. Research samples limited on higher education sector in Indonesia, so the result couldn’t generalize for all public sectors in Indonesia.